Book Reviews - Lindsay, Robert; Grant, H. Roger; Frey, Marsha L.; Reilly, John T.; Marran, James F.; Enders, Victoria L.; Tate, Benjamin; Banner-Haley, Charles T.; Boland, Brian; Slater, Peter Gregg; Armstrong, Thomas F.; Ellis, Ann W.; et al. (Teaching History: A Journal of Methods, 1989)
Martin K. Sorge. The Other Price of Hitler's War. German Military and Civilian Losses Resulting from World War II. Westport, CT: Greenwood Press, 1986. Pp. xx, 175. Cloth, $32.95; M. K. Dziewanowski. War At Any Price: World War II in Europe, 1939-1945. Englewood Cliffs, NJ: Prentice-Hall, 1987. Pp. xiv, 386. Paper, $25.67. Review by Lawrence S. Rines of Quincy Community College. David Goldfield. Promised Land: The South Since 1945. Arlington Heights, IL: Harlan Davidson, Inc., 1987. Pp. xiii, 262. Cloth, $19.95, Paper, $9.95; Alexander P. Lamis. The Two Party South. New York: Oxford University Press, 1984. Pp. x, 317. Cloth, $25.00; Paper, $8.95. Review by Ann W. Ellis of Kennesaw College. Walter J. Fraser, Jr., R. Frank Saunders, Jr., and Jon L. Wakelyn, eds. The Web of Southern Social Relations: Women, Family, and Education. Athens: University of Georgia Press, 1985. Pp. XVII, 257. Paper, $12.95. Review by Thomas F. Armstrong of Georgia College. William H. Pease and Jane H. Pease. The Web of Progress: Private Values and Public Styles in Boston and Charleston, 1828-1842. New York and Oxford: Oxford University Press, 1985. Pp. xiv, 334. Paper, $12.95. Review by Peter Gregg Slater of Mercy College. Stephen J. Lee. The European Dictatorships, 1918-1945. London and New York: Methuen, 1987. Pp. xv, 343. Cloth, $47.50; Paper, $15.95. Review by Brian Boland of Lockport Central High School, Lockport, IL. Todd Gitlin. The Sixties: Days of Hope, Days of Rage. New York: Bantam, 1987. Pp. 483. Cloth, $19.95; Maurice Isserman. IF I HAD A HAMMER... : The Death of the Old Left and the Birth of the New Left. New York: Basic Books, 1987. Pp. xx, 244. Cloth, $18.95. Review by Charles T. Banner-Haley of Martin Luther King, Jr. Center for Nonviolent Social Change, Inc. Donald Alexander Downs. Nazis in Skokie: Freedom, Community, and the First Amendment. Notre Dame IN: Notre Dame Press, 1985. Pp. 227. Paper, $9.95. Review by Benjamin Tate of Macon Junior College. Paul Preston, The Triumph of Democracy in Spain. London and New York: Methuen, 1986. Pp. 227. Cloth, $32.00. Review by Victoria L. Enders of Northern Arizona University. Robert B. Downs. Images of America: Travelers from Abroad in the New World. Urbana and Chicago: University of Illinois Press, 1987. Pp. 232. Cloth, $24.95. Review by James F. Marran of New Trier Township High School, Winnetka, IL. Joel H. Silbey. The Partisan Imperative: The Dynamics of American Politics Before the Civil War. New York and Oxford: Oxford University Press, 1985. Pp. viii, 234. Paper, $8.95. Review by John T. Reilly of Mount Saint Mary College. Barbara J. Howe, Dolores A. Fleming, Emory L. Kemp, and Ruth Ann Overbeck. Houses and Homes: Exploring Their History. Nashville: The American Association for State and Local History, 1987. Pp. xii, 168. Paper, $13.95; $11.95 to AASLH members. Review by Marsha L. Frey of Kansas State University. Thomas C. Cochran. Challenges to American Values: Society, Business and Religion. New York and Oxford: Oxford University Press, 1987. Pp. 147. Paper, $6.95. Review by H. Roger Grant of University of Akron. M.S. Anderson. Europe in the Eighteenth Century, 1713-1783. London and New York: Longman, 1987. Third Edition. Pp. xii, 539. Cloth, $34.95. Review by Robert Lindsay of the University of Montana.